You are on page 1of 4

Homework #1

1.4 (a) Guess a formula for 1 +3 +5 + +(2n 1) by evaluating the sum for n = 1, 2, 3,
and 4.
(b) Prove your formula using mathematical induction.
Solution: (a) Lets make a table
n 1 + 3 + + (2n 1)
1 1 = 1
2 1 + 3 = 4
3 1 + 3 + 5 = 9
4 1 + 3 + 5 + 7 = 16
It look like the formula is 1 + 3 + + (2n 1) = n
2
(b) We did the base case in part (a): 1 = 1
2
. For the inductive step, we assume 1 + 3 +
+(2k 1) = k
2
and use that to prove 1 +3 + +(2k 1) +(2(k +1) 1) = (k +1)
2
.
Well,
1 + 3 + + (2k 1) + (2(k + 1) 1) =
_
1 + 3 + + (2k 1)
_
+ (2(k + 1) 1) =
k
2
+ (2(k + 1) 1) by the inductive hypothesis. But
k
2
+ 2(k + 1) 1 = k
2
+ 2k + 2 1 = k
2
+ 2k + 1 = (k + 1)
2
, as required.
By induction, therefore, 1 + 3 + + (2n 1) = n
2
.
1.6 Prove that 11
n
4
n
is divisible by 7 when n is a natural number.
Proof: We use induction.
Base case n = 1: 11
1
4
1
= 11 4 = 7, which is divisible by 7.
Inductive step. Assume 11
k
4
k
= 7m for some integer m and show that
11
k+1
4
k+1
is divisible by 7.
Well, 11
k+1
4
k+1
= 11 11
k
4 4
k
= 11 11
k
11 4
k
+ 11 4
k
4 4
k
= 11(11
k
4
k
) + (11 4)4
k
= 11(7m) + 7 4
k
= 7(11m + 4
k
)
Which is divisible by 7. By induction, therefore, 11
n
4
n
is divisible by 7 for any natural
number n.
1.11 For each n N, let P
n
denote the assertion n
2
+ 5n + 1 is an even integer.
(a) Prove that P
n+1
is true whenever P
n
is true.
(b) For what n is P
n
actually true? What is the moral of this exercise?
Solution: (a) Assume n
2
+ 5n + 1 = 2m and show that (n + 1)
2
+ 5(n + 1) + 1 is even.
Well,
(n + 1)
2
+ 5(n + 1) + 1 = n
2
+ 2n + 1 + 5n + 5 + 1 = (n
2
+ 5n + 1) + 2n + 6
= (2m) + 2n + 6 = 2(m + n + 3)
which is even. That is, weve shown that P
n+1
follows from P
n
.
(b) There are no natural numbers for which P
n
is true. Well do two arguments; one
for n even and one for n odd.
Suppose n is even, so n = 2m for some natural number m. Then
n
2
+5n+1 = (2m)
2
+5(2m)+1 = 4m
2
+10m+1 = 2(2m
2
+5m)+1 = even+odd = odd
Suppose n is odd, so n = 2m1 for some natural number m. Then
n
2
+ 5n + 1 = (2m1)
2
+ 5(2m1) + 1 = 4m
2
4m + 1 + 10m5 + 1
= 4m
2
+ 6m3 = 2(2m
2
+ 3m) 3 = even odd = odd
In either case, P
n
is false. The moral of this exercise is: Dont forget I
1
, the base case.
1.12 The binomial theorem asserts that (a + b)
n
=
n

k=0
_
n
k
_
a
nk
b
k
.
(a) Verify the binomial theorem for n = 1, 2, and 3.
(b) Show that
_
n
k
_
+
_
n
k 1
_
=
_
n + 1
k
_
.
(c) Prove the binomial theorem using mathematical induction and part (b).
Solution: (a) For n = 1, we have (a + b)
1
=
_
1
0
_
a
10
b
0
+
_
1
1
_
a
11
b
1
= a + b, which
checks.
For n = 2, we know (a + b)
2
= a
2
+ 2ab + b
2
. The theorem asserts that
(a + b)
2
=
_
2
0
_
a
20
b
0
+
_
2
1
_
a
21
b
1
+
_
2
2
_
a
22
b
2
=
2!
(0!)(2!)
a
2
+
2!
(1!)(1!)
ab +
2!
(2!)(0!)
b
2
= a
2
+ 2ab + b
2
.
For n = 3, we know that (a + b)
3
= a
3
+ 3a
2
b + 3ab
2
+ b
3
. The theorem says
(a + b)
3
=
_
3
0
_
a
30
b
0
+
_
3
1
_
a
31
b
1
+
_
3
2
_
a
32
b
2
+
_
3
3
_
a
33
b
3
=
3!
(0!)(3!)
a
3
+
3!
(1!)(2!)
a
2
b +
3!
(2!)(1!)
ab
2
+
3!
(3!)(0!)
b
3
= a
3
+ 3a
2
b + 3ab
2
+ b
3
.
(b) Well,
_
n
k
_
+
_
n
k 1
_
=
n!
k!(n k)!
+
n!
(k 1)!(n (k 1))!
=
n!
k!(n k)!
+
n!
(k 1)!(n k + 1)!
=
n!(n k + 1)
k!(n k)!(n k + 1)
+
n!k
k(k 1)!(n k + 1)!
=
n!(n k + 1)
k!(n k + 1)!
+
n!k
k!(n k + 1)!
=
n!(n k + 1) + n!k
k!(n k + 1)!
=
n!(n k + 1 + k)
k!(n k + 1)!
=
n!(n + 1)
k!(n + 1 k)!
=
(n + 1)!
k!((n + 1) k)!
=
_
n + 1
k
_
as required.
(c) The base case has been more than adequately done in part (a), so we proceed to the
inductive step: Assume that (a + b)
n
=
n

k=0
_
n
k
_
a
nk
b
k
and show that (a + b)
n+1
=
n+1

k=0
_
n + 1
k
_
a
(n+1)k
b
k
.
Well, (a+b)
n+1
= (a+b)(a+b)
n
= (a+b)
n

k=0
_
n
k
_
a
nk
b
k
by the inductive hypothesis.
We distribute to obtain
n

k=0
_
n
k
_
a
nk+1
b
k
+
n

k=0
_
n
k
_
a
nk
b
k+1
= a
n+1
+
n

k=1
_
n
k
_
a
nk+1
b
k
+
n1

k=0
_
n
k
_
a
nk
b
k+1
+ b
n+1
Let j = k + 1 (so k = j 1) in the second summation to get:
= a
n+1
+
n

k=1
_
n
k
_
a
nk+1
b
k
+
n

j=1
_
n
j 1
_
a
n(j1)
b
j
+ b
n+1
Now let j = k in the rst summation:
= a
n+1
+
n

j=1
_
n
j
_
a
nj+1
b
j
+
n

j=1
_
n
j 1
_
a
nj+1
b
j
+ b
n+1
= a
n+1
+
n

j=1
__
n
j
_
+
_
n
j 1
__
a
nj+1
b
j
+ b
n+1
By part (b), this is:
= a
n+1
+
n

j=1
_
n + 1
j
_
a
nj+1
b
j
+ b
n+1
=
_
n + 1
0
_
a
n+1
+
n

j=1
_
n + 1
j
_
a
nj+1
b
j
+
_
n + 1
n + 1
_
b
n+1
=
n+1

k=0
_
n + 1
k
_
a
(n+1)k
b
k
, as required.
2.4 Show that
_
5

3
_
1/3
does not represent a rational number.
Solution: Let a =
_
5

3
_
1/3
. Then
a
3
= 5

3
a
3
5 =

3
(a
3
5)
2
= 3
a
6
10a
3
+ 22 = 0
That is, a is a root of the polynomial f(x) = x
6
10x
2
+22. By Theorem 2.2, the possible
rational roots of f are 1, 2, 11 and 22. Mental substitution shows that none of
these is a root of f, so f has no rational roots at all. That is, all its roots are irrational,
so in particular, a is irrational.
2.6 Discuss why 4 7b
2
must be a rational number if b is rational.
Solution: The quick answer is that the rational numbers are a eld, so they are closed
under ordinary arithmetic (addition, subtraction, multiplication, division). Hence,
4 7b
2
= rational (rational)(rational)
2
is rational.
More explicitly, if b is rational, then b =
p
q
where p and q are integers. So
4 7b
2
= 4 7
_
p
q
_
2
=
4q
2
7p
2
q
2
=
integer
integer
is a rational number. (Since the integers are closed under +, and ).

You might also like